2014
DOI: 10.1016/j.ijheh.2014.03.004
|View full text |Cite|
|
Sign up to set email alerts
|

Maternal arsenic exposure and birth outcomes: A comprehensive review of the epidemiologic literature focused on drinking water

Abstract: Inorganic arsenic (iAs) is a human toxicant to which populations may be exposed through consumption of geogenically contaminated groundwater. A growing body of experimental literature corroborates the reproductive toxicity of iAs; however, the results of human studies are inconsistent. Therefore, we conducted a comprehensive review of epidemiologic studies focused on drinking water iAs exposure and birth outcomes to assess the evidence for causality and to make recommendations for future study. We reviewed 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 77 publications
1
34
0
2
Order By: Relevance
“…A growing body of epidemiologic evidence suggests increased risks for adverse birth outcomes in association with the use of highly iAs contaminated water sources by pregnant women (> 10 μg/L), including the delivery of lower birth weight babies at term [21, 22], in Argentina [23], Bangladesh [24, 25], India [26, 27], Mexico [28], and Taiwan [29]. Shorter birth length [28, 30] and smaller head and chest circumferences [25] have also been reported among mothers with high level iAs exposure.…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of epidemiologic evidence suggests increased risks for adverse birth outcomes in association with the use of highly iAs contaminated water sources by pregnant women (> 10 μg/L), including the delivery of lower birth weight babies at term [21, 22], in Argentina [23], Bangladesh [24, 25], India [26, 27], Mexico [28], and Taiwan [29]. Shorter birth length [28, 30] and smaller head and chest circumferences [25] have also been reported among mothers with high level iAs exposure.…”
Section: Introductionmentioning
confidence: 99%
“…An increasingly important source of exposure to inorganic arsenic is food, such as cereals, crops, and vegetables, which are cultured in arsenic-rich areas where farmers use groundwater for irrigation or in areas with historic arsenic-based pesticide usage. Both epidemiological and animal studies showed that arsenic exposure causes adverse developmental effects such as fetal loss, infant death, low intelligence quotient scores, reduced birth weight, and reduced weight gain (Calderon et al , 2001; Rodriguez et al , 2002; Wang et al , 2006a; Huyck et al , 2007; Rahman et al , 2007; Li et al , 2009; Bloom et al , 2014), suggesting that arsenic exposure impacts development.…”
Section: Introductionmentioning
confidence: 99%
“…5 DSÖ'nün (2016) Antenatal Bakım Rehberi'nde, rutin dopler ultrason önerilmemektedir. Bununla birlikte 24. gebelik haftasından önce gestas yonel gebelik haftasını belirlemek, çoğul gebelikleri ve fetal anomaliyi saptamak amacıyla ultrason izlemi yapılabileceği belirtilmiştir.…”
Section: Ruti̇n Ultrason İzlemi̇unclassified
“…(2014) tarafından toplam 18 çalış-manın incelendiği bir çalışma da bebek doğum ağırlığı ve gestasyonel yaş ile arsenikli içme suyunun ilişkisi incelenmiştir. 24 Araştırma sonucunda düşük doğum ağırlığı ve preterm doğum riskinde artma olduğuna dair kanıtların yetersiz olduğu ve bebeğin doğum kilosunun azalmasıyla arsenikli içme suyu arasındaki bağlantıya dair kanıtların minimal düzeyde olduğu belirtilmiştir. 24 Antenatal takiplerde ebeler, gebelere içme suyunun içerisindeki elementlere karşı duyarlı olmaları konusunda bilgilendirme yapmalı ve kanıta dayalı çalışmaların sonuçlarını onlara aktararak gebeleri aydınlatmalıdır.…”
Section: İçme Suyumuz Anne Ve Bebek İçi̇n Güveni̇li̇r Mi̇?unclassified